Hipnoterapi, Relevansinya Dalam Mempengaruhi Hidup Manusia : Tinjauan Literatur yang sistematis - Fitri Isnaini, Nurdiana; Verlandes, Yuliasnita; Hadi Purnomo, Agoes (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2024)
In life, humans have various targets that cause stress in their lives. Not to mention teenagers, with all their phenomena they have high pressure related to social life, in learning activities or parental expectations that do not match their expectations. The purpose of this study is to determine the relevance of hypnotherapy in helping to solve problems faced by humans, especially teenagers. With the stages of treatment and therapy, it will be known how hypnotherapy intervenes in the mindset and lifestyle of teenagers. Furthermore, based on the results of observations from literacy, the impact that appears along with the treatment carried out by hypnosis on clients is known. Using a systematic literacy study research method, this study provides results that the treatment is carried out with the following stages; Preinduction interview, Deepening, Termination, Depth level test (hypnotherapy depth test) and Post hypnotic behavior (post-hypnosis behavior). These stages are to ensure the optimization of the therapeutic impact carried out by hypnosis on clients. The relevance of hypnotherapy to reduce stress in adolescents according to the referenced article is significant based on the results of the ANOVA and t-test statistical tests carried out on each article, with a p value: 0.000; <.001; <.01; and <0.02. Hypnotherapy techniques that can be used to reduce stress in adolescents are basic hypnotherapy, group hypnotherapy, self hypnotherapy, and combined hypnotherapy such as hypnotherapy with augmented reality technology (AR) and Mindful hypnotherapy (MH).